Buschke-Löwenstein Tumour: Successful Treatment with Minimally Invasive Techniques - Estefânia Correia; António Santos (Hindawi Limited, 2015)
We report a case of an 80-year-old female who presented with a four-year history of a growing mass in the perianal area with pain and bleeding during defaecation. Clinical examination revealed a locally destructive, cauliflower-like, verrucous mass measuring 10 × 12 cm in diameter. Histologic findings revealed a moderate degree of dysplasia of the epithelium with koilocytosis atypia, acanthosis, and parakeratosis, features that are consistent with Buschke-Löwenstein tumour. Polymerase-chain-reaction assay for human papillomavirus (HPV) showed an infection with HPV type 11. Full-thickness excision of involved skin was undertaken by cryotherapy and electrocautery over five months. The entire wound was left open to heal by secondary intention. After 3 years of follow-up, the patient has not experienced a recurrence, with excellent functional results, but the cosmetic results were satisfactory. These minimally invasive techniques can be safer and more cost-effective than surgery and the General Practitioner can play a key role in diagnosis.